Arab Internationalism and Gender: Perspectives from the Third Session of the United Nations Commission on the Status of Women, 1949. (6th July 2016) - Robinson, Nova
Abstract : Historians of the Middle East have used gender to explore a range of topics, from how crises around gendered practices have contributed to the construction of national identities to women's roles in nationalist movements. Whereas early gender histories focused on single nation-states, recent scholarship has turned to regional and transnational connections. Yet the international sphere, the domain of nation-states and nongovernmental organizations in relation to each other, has yet to be examined through the lens of gender. In this essay, I argue that doing so yields new insights into the relationship between the national and the international in the Middle East, and into the process of rights claiming in postcolonial nation-states. I make this argument through a discussion of the third session of the United Nations Commission on the Status of Women (UNCSW).